Discovery of a new palladacycle precatalyst and its applications to C–O coupling reactions between electron-deficient phenols and functionalized heteroaryl chlorides. Issue 18 (29th April 2015) - Zhang, Ting; Tudge, Matthew T.
Graphical abstract: Abstract: A new palladacycle precatalyst (J009 PreCat ) was designed and synthesized. The precatalyst dramatically improved the yield of a class of extremely challenging cross-coupling reactions between functionalized heteroaryl chlorides and electron-deficient phenols. The reactions are easy to set up, are tolerant of various functional groups, and allow quick access to electron-deficient, highly functionalized diaryl ether compounds.